Pengaruh Kerjasama Tim, Beban Kerja, dan Disiplin Kerja Terhadap Produktivitas Kerja Karyawan PT Sejin Fashion Indonesia Pati - Riska Amelia; Ninik Dwi Atmini; Heri Usodo; Rita Andini; Adji Seputro (Prosiding Seminar Nasional Ilmu Manajemen Kewirausahaan dan Bisnis, 2025)
This study aims to analyze the effect of teamwork, workload, and work discipline on the work productivity of employees at PT Sejin Fashion Indonesia Pati. The study used a sample of 94 respondents determined using proportionate stratified random sampling. Data collection was conducted using questionnaires and analyzed using multiple linear regression through SPSS version 25, including validity and reliability tests, t-tests, F-tests, and determination coefficients. The results show that: 1) teamwork has a positive and significant effect on employee productivity; 2) workload has a positive and significant effect on employee productivity; and 3) work discipline has a positive and significant effect on employee productivity; 4) teamwork, workload, and work discipline have a simultaneous effect on employee productivity. Work discipline is the most dominant variable in increasing employee work productivity. These findings imply that strengthening teamwork, adjusting workloads, and improving employee discipline are important strategies for companies to increase employee work productivity.